Le rouge et le noir: implications of early pigment use in Africa, the near East and Europe for the origin of cultural modernity - (:unkn) unknown (My University, 2008)
The increase in the frequency of ochre recovered from African Middle Stone Age sites has been used, along with other discerned changes in hominid behaviour, to support the hypothesis that modern cognitive abilities gradually arose gradually in Africa, in conjunction with the biological changes that mark the origin of our species. In order to assess this hypothesis I review the earliest evidence for the use of pigmentatious material in Africa, the Near East and Europe and discuss its evolutionary significance. This review indicates that the earliest, still unresolved, use of pigments at African sites is possibly associated with archaic Homo sapiens and not with anatomically modern humans; it thus breaks the link, established by the Out of Africa scenario, between biological and cognitive change. This link is also challenged by the systematic use of black pigments by European Neanderthals prior to contact with anatomically modern humans. Ongoing analysis of manganese pieces from Neanderthal sites indicates use that is consistent with symbolic activities.
Keywords: African Research